Supratentorial primitive neuroectodermal tumor presenting with intracranial hemorrhage in adult - Abuzayed, Bashar (Medknow Publications & Media Pvt Ltd, 2014)
A 24-year-old female patient presented with complaints of nausea, vomiting and of loss of consciousness lasted for 15 minutes with left sided weakness. Neuroradiological evaluation revealed a hemorrhagic mass lesion in the right frontal lobe. The patient was operated and intraoperative findings showed a cortical-subcortical hematoma including hemorrhagic and disrupted tissue with a pathologic purple tissue on the periphery of the hematoma. Postoperative course was uneventful and postoperative histopathological examination revealed primitive neuroectodermal tumor. The patient was then referred to medical and radiation oncology clinics for further evaluation and treatment.